Piperidine-3, 4-diol and piperidine-3-ol derivatives of pyrrolo[2, 1-f][1, 2, 4]triazine as inhibitors of anaplastic lymphoma kinase. Issue 5 (1st March 2015) - Mesaros, Eugen F.; Angeles, Thelma S.; Albom, Mark S.; Wagner, Jason C.; Aimone, Lisa D.; Wan, Weihua; Lu, Lihui; Huang, Zeqi; Olsen, Mark; Kordwitz, Emily; Haltiwanger, R. Curtis; Landis, Amy J.; et al.
Graphical abstract